THE EFFECT OF PRICE AND PRODUCT QUALITY ON THE DECISION TO BUY A LAPTOP BRAND ACER STUDENT STIE "KBP" PADANG - Olanda, Septika; Badri, Juarsa (Bina Bangsa International Journal of Business and Management, 2022)
This study aims to determine (1) the effect of price on laptop purchasing decisions, (2) product quality affect laptop purchasing decisions, (3) price and product quality affect laptop purchasing decisions. The variables in this study are the independent variables, namely price (X₁) and product quality (X₂) and the dependent variable (Y) namely purchasing decisions. This study uses a quantitative research design with multiple linear regression data analysis. The results of the research that From the calculation of the t test, it can be seen that for X₁, t significant value is 0.038 <0.05 for N = 94, so the conclusion is that the hypothesis can be accepted or proven true for the price variable (X₁).  So it can be stated that there is a negative and significant influence between price and purchasing decisions.  While the t test for X₂, the significant value is 0.018<0.05 for N = 94, the conclusion is also the hypothesis is accepted for the product quality variable (X₂).  So it can be stated that there is a positive and significant influence between product quality and purchasing decisions